The Interplay of Lyrics and Melody in Conveying Emotional Narratives: A Case Study of Niki Zefanya’s Selected Songs (Backburner, Take A Chance with Me, Ocean & Engines) - Avanti Nur Febrianingsih; Yanti Rosalinah (Universitas Islam Negeri Palopo, 2025)
This study discusses the relationship between lyrics and melody in expressing emotional narratives in NIKI Zefanya’s selected songs, namely Backburner, Take a Chance With Me, and Oceans & Engines. The purpose of this study is to explain how lyrics and melody work together to show emotional meaning. The method used in this research is qualitative descriptive. The data used are from the lyrics and musical elements of the three songs. This study uses lyrical analysis and musical semiotics to identify language and music features that express emotions. Results indicate that metaphor, hyperbole, and irony are the most frequently used figurative devices in the lyrics. Tonal variation, rhythm, and harmony further enhance the emotional expression conveyed in the songs. The combination of these elements creates a strong emotional connection between the songs and the listeners. This study gives a better understanding of how emotions are built through the combination of lyrics and melody in popular music.